Counseling on the Benefits of BPJS Kesehatan Membership to the Community in Mojosongo, Jebres, Surakarta - Kusumawardhani, Oktavy Budi; Saputra, Raihan Alif; Adriana, Nadya Puspita; Wicaksono, Dipo (Universitas Muhammadiyah Surakarta, 2023)
BPJS Health is a public legal entity that is responsible to the president and functions to administer the health insurance program for all Indonesian residents, including foreigners who work for a minimum of 6 months in Indonesia. BPJS Health ensures that participants receive health maintenance and protection benefits in order to meet their basic health needs. The purpose of this service is to explain the benefits of BPJS Kesehatan membership. The place where the service is carried out is in the Surakarta City area on June 2022. The service uses lecture and discussion methods with the community. As a result of this service, the community's understanding of the benefits of BPJS Health membership has grown. obtained from the results of the pre-test value of 50% and the post-test value of 90%. Conclusion: The community is expected to make more use of its BPJS Health membership in supporting health and getting the best health service facilities.